Praxis in the City: Care and (Re)Injury in Belfast and Orumiyeh. Issue 2 (4th March 2018) - Dowler, Lorraine; Ranjbar, A. Marie
Abstract : This article builds on the geographic literature of nonviolence with the feminist literature of care ethics and positive security to explore the potential for a praxis that promotes relational urban social justice. We examine two cities—Belfast, Northern Ireland, and Orumiyeh, Iran—that have historically endured political struggles that continue to undermine the quality of urban life. We analyze vulnerability to political, environmental, and infrastructural violence in these two urban landscapes with an eye toward "just praxis" and "positive security, " as we outline the ways in which Belfast and Orumiyeh are reinjured by institutional practices that purportedly seek urban social justice. First, we argue for the importance of care praxis in the light of the entanglement of a murder investigation with the Boston College oral history program "The Belfast Project, " which recorded testimony from former and current members of paramilitary groups. Second, we examine an environmental justice movement in Orumiyeh, where activists navigate a contested political terrain shaped by state violence toward ethnic minorities and punitive economic sanctions from the international community. From this perspective, a just praxis acknowledges the ubiquity of violent conflict while it distinguishes global readings that occur from a distance to the intimate and interminable experiences of violence that take place in urban places. We argue that a more critical engagement with the relationship between care and vulnerability reveals the enormous potential of imagining geographies of existing and evolving relationalities of care rather than global assumptions from afar about vulnerable communities.